2022
DOI: 10.34208/jba.v24i1.1401
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Earnings Quality

Abstract: The research aims to obtain empirical evidence about factors that affect earnings quality, particularly, the influence of auditor size, audit tenure, audit specialization, firm size, audit committee, leverage, investment opportunity set (IOS), growth opportunity, managerial ownership, and institutional ownership on earnings quality. The population used in this research are all manufacturing companies that are listed in Indonesia Stock Exchange from 2014-2020 and use purposive sampling as the sampling method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…Contrary to the research result, leverage has been shown to have a negative impact on a company's earnings quality (Alvin and Susanto 2022;Listyaningsih 2020). The greater the leverage of an entity, then the earnings quality will be smaller (Pratama and Sunarto 2018;Dewi, Endiana, and Arizona 2020).…”
Section: Introductionmentioning
confidence: 77%
“…Contrary to the research result, leverage has been shown to have a negative impact on a company's earnings quality (Alvin and Susanto 2022;Listyaningsih 2020). The greater the leverage of an entity, then the earnings quality will be smaller (Pratama and Sunarto 2018;Dewi, Endiana, and Arizona 2020).…”
Section: Introductionmentioning
confidence: 77%
“…Theo nghiên cứu Al-Shammari & Al-Sultan (2010), Rusmin (2011), số lượng thành viên ban kiểm soát có liên quan đến tính trung thực báo cáo tài chính và làm giảm các gian lận và sai sót. Một bộ phận chức năng với nhiều thành viên có thể sẽ có sự đa dạng về chuyên môn và kinh nghiệm, sẽ nâng cao được hiệu quả giám sát, từ đó nâng cao tính trung thực của báo cáo tài chính.…”
Section: ảNh Hưởng Của Quy Mô Ban Kiểm Soát đếN Tính Trung Thực Của B...unclassified
“…Earnings quality is important and crucial information for shareholders and other stakeholders. Alvin & Susanto (2022) assert that the earnings quality reflects how effectively a company's profits can provide valuable and useful information to the public. This quality significantly influences decision-making and aids shareholders in evaluating the company's performance.…”
Section: Earnings Qualitymentioning
confidence: 99%